PERANAN ECONOMIC VALUE ADDED (EVA) DALAM MENGUKUR KINERJA PERUSAHAAN - Lee Hiang (Center for Economic Studies Universitas Katolik Parahyangan, 2008)
As the economic condition becoming more global, business competition is becoming tighter. Effectiveness and efficiency have become very important things. companies also need bigger capital in order to sustain in the competition. Companies can get higher capital by issuing stocks to the market. This condition has been a challenge for the companies to attract investors to invest their funds in their companies. in this effort, companies shouldn't only describe their performance financial statements, but also by performance measurement such as Economic value Added (EVA). EVA can help managers to improve their performance and provide consideration for the investors